Culturally relevant constructionist design: exploring the role of community in identity development. Issue 11 (20th August 2020) - Thanapornsangsuth, Sawaros; Holbert, Nathan
Abstract : Purpose: Many initiatives seek to engage children in maker education. However, there is a paucity of research examining children's engagement in making in low-income formal school settings. Likewise, little work has been done to explore the transformative perspectives of both the children and the people around them. This study aims to explore a Culturally Relevant Constructionist Design framework that emphasizes making as a way of building connections to ones' community. The participants' shifting perspectives and receptivity in engaging in maker activities that involve making inventions for their community, inspired by the nation's most beloved figure, King Bhumibol are evaluated. Design/methodology/approach: This study investigates fourth-grade students, a teacher and community members around a public school in Thailand. Using qualitative research methods, data collection includes interviews, field notes observation, photos and videos of the sessions. This paper presents three case studies that represent the shifting perspectives and receptivity of teachers, community members and students through engaging in making experience. The first case illustrates the ways in which building for others supports the students' formation of an identity of a creator. The two cases describe a teacher and a community member who developed new-found perceptions of students as valuable contributors to the community. Findings: The findings highlight making inventions for the community as ways to connect teachers, community members and students together. The study also identifies key perceptions and experiences that empower students' as contributors to their community. Through the process of making, the teacher and the community members also developed new-found positive perspectives of the students. Particularly, they viewed the students beyond traditional school performance metrics, and considered their other latent abilities. Practical implications: This study discusses these findings in light of previous research on maker education especially in low-income communities. It also showcases the role of making for the betterment of the community as a tool for engendering change in schools and empowering students to design and make personally and socially meaningful projects. The study also highlights how design-based research carried out in the international context, particularly in Thai locality and classrooms. Originality/value: This study argues against the deficit lens that assumes a low sense of expectation for what students from lower-income schools can do. Students hold unique worldviews that lead them to create innovations relevant to their local and cultural needs. The study addresses this gap by designing a framework that emphasizes making relevant cultural connections to students' communities. The study also showcases maker-centered experiences that enable students to express their ideas, to cultivate relationships, to help others and to see themselves in new ways. The perspectives of the participants hold implications beyond the predominant focus of maker education initiatives.